Reading preference and motivation elements in reading habit research / Muslim Ismail-Ahmad ... [et al.] - Ismail-Ahmad, Muslim; Bardan, Muhammad Zaidie; Mohd Radwan, Rizana; Sarmin Panut, Nurul Farihah (Faculty of Information Management, 2022)
This conceptual paper examines the research conducted on university students' reading habits over the past three years. Several pertinent questions, facts, and figures were extracted from the accumulated material. These statistics are essential for university library management with limited resources and funds. Reading preferences questions inquire about the purpose of their reading, whether for leisure, information gathering, or academic requirements. Paper versus digital reading preferences is among the most frequently asked about themes. The highlights include the time of day, how long, and where you prefer to read. This concept paper also addresses the subject of why digital reading is preferred.